Notch Signaling Pathway Is Activated by Sulfate Reducing Bacteria - Singh, Sudha B.; Coffman, Cristina N.; Carroll-Portillo, Amanda; Varga, Matthew G.; Lin, Henry C. (Frontiers in Cellular and Infection Microbiology, 2021)
Sulfate Reducing Bacteria (SRB), usually rare residents of the gut, are often found in increased numbers (called a SRB bloom) in inflammatory conditions such as Inflammatory Bowel Disease (IBD), pouchitis, and periodontitis. However, the underlying mechanisms of this association remain largely unknown. Notch signaling, a conserved cell-cell communication pathway, is usually involved in tissue development and differentiation. Dysregulated Notch signaling is observed in inflammatory condition such as IBD. Lipopolysaccharide and pathogens also activate Notch pathway in macrophages. In this study, we tested whether Desulfovibrio, the most dominant SRB genus in the gut, may activate Notch signaling. RAW 264.7 macrophages were infected with Desulfovibrio vulgaris (DSV) and analyzed for the expression of Notch signaling pathway-related proteins. We found that DSV induced protein expression of Notch1 receptor, Notch intracellular domain (NICD) and p21, a downstream Notch target, in a dose-and time-dependent manner. DSV also induced the expression of pro-IL1b, a precursor of IL-1b, and SOCS3, a regulator of cytokine signaling. The gamma secretase inhibitor DAPT or Notch siRNA dampened DSV-induced Notch-related protein expression as well the expression of pro-IL1b and SOCS3. Induction of Notch-related proteins by DSV was not affected by TLR4 -IN -C34(C34), a TLR4 receptor antagonist. Additionally, cell-free supernatant of DSV-treated macrophages induced NICD expression in uninfected macrophages. DSV also activated Notch pathway in the human epithelial cell line HCT116 and in mouse small intestine. Thus, our study uncovers a novel mechanism by which SRB interact with host cells by activating Notch signaling pathway. Our study lays a framework for examining whether the Notch pathway induced by SRB contributes to inflammation in conditions associated with SRB bloom and whether it can be targeted as a therapeutic approach to treat these conditions.